Analyzing The Role of Migration Phenomenon on The Human Development Index of The City, Case Study: Bojnord City - Sedaghati, Atefeh; Talebkhah, Hamid (International Journal of Sustainable Construction Engineering and Technology, 2023)
One of the UN’s Human Development Reports on Migration shows that the negative impact of migrants on host communities is inconsistent with reality. The main message of the Human Development Report is that the benefits of human development can be reaped by reducing barriers to mobility and improving the treatment of migrants. The present study is done, using a descriptive-analytical method of applied studies. This study tries to calculate and analyze the Human Development Index (HDI) during the official general census of the country in 2006, 2011 and 2016 and do a comparative study among "population of the province", "urban areas of the county" and "immigrants" in the county of Bojnord, using two possible methods of calculation and analysis of this index (Natural and geometric method in addition to changes in the type of data in accordance with the old and new method proposed by the United Nations and contained in valid scientific texts in calculating the human development index). According to the findings, migration has not reduced the human development index, and has also grown at all three levels. On the other hand, the results show that migration is not necessarily associated with negative consequences and, conversely, has been able to accelerate development in the host society, and this is because the nature of modern migration is more related to improving one’s position in society and human mobility than simply respond to the basic instincts of survival. The index calculated for immigrants in 2016 (0.752) was more than the other two periods (0.744 and 0.7); While the number of immigrants entering the urban areas of the county was less than the previous two periods. In general, the development index of 2011 and 2016 is more than 2006, due to the opportunities created by the centralization of Bojnord in 2005.